2003
DOI: 10.1051/0004-6361:20030532
|View full text |Cite
|
Sign up to set email alerts
|

Galactic structure studies with BATC star counts

Abstract: Abstract.We report the first results of star counts carried out with the National Astronomical Observatories (NAOC) • 49 00 .0 (J2000) (Galactic coordinates: l = 169.95The field of view is 0.95 deg 2 , and the spatial scale was 1 .67. Since star counts at high galactic latitudes are not strongly related to the radial distribution, they are well suited to study the vertical distribution of the Galaxy. In our model, the distribution of stars perpendicular to the plane of the Galaxy is given by two exponential … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
40
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 69 publications
6
40
0
Order By: Relevance
“…Recently, Chen et al (2001) found 330 ± 3 pc, while Du et al (2003) found 320 ± 15 pc. Our value of 120 pc is much smaller than those.…”
Section: General Comparisonmentioning
confidence: 99%
“…Recently, Chen et al (2001) found 330 ± 3 pc, while Du et al (2003) found 320 ± 15 pc. Our value of 120 pc is much smaller than those.…”
Section: General Comparisonmentioning
confidence: 99%
“…We used the classical χ 2 statistic to estimate galactic model parameters, which is the most commonly method in recent studies (Phleps et al 2000(Phleps et al , 2005Chen et al 2001;Siegel et al 2002;Du et al 2003Du et al , 2006Jurić et al 2008;Bilir et al 2008a). The comparison of the logarithmic density functions derived from the observations and the analytical density laws is given in Fig.…”
Section: Estimation Of the Galactic Model Parametersmentioning
confidence: 99%
“…We used the classical χ 2 method for the estimation of the Galactic model parameters, a method which is made in the studies of the Galactic structure that has been used in the determination of the most recent numerical values for the Galactic model parameters (Phleps et al 2000(Phleps et al , 2005Chen et al 2001;Siegel et al 2002;Du et al 2003Du et al , 2006Jurić et al 2008). The comparison of the logarithmic density functions derived from the observations and the analytical density laws are given in Figure 7, for four fields with Galactic longitudes l = 0, 90, 180 and 270 • .…”
Section: Estimation Of the Galactic Model Parametersmentioning
confidence: 99%